Divergent Ventilatory and Blood Pressure Responses are Evident Following Repeated Daily Exposure to Mild Intermittent Hypoxia in Males with OSA and Hypertension - Panza, Gino S.; Puri, Shipra; Lin, Ho-Sheng; Mateika, Jason H. (Frontiers in Physiology, 2022)
Introduction: Resting minute ventilation and ventilation during and following hypoxia may be enhanced following daily exposure to mild intermittent hypoxia (MIH). In contrast, resting systolic blood pressure (SBP) is reduced following daily exposure to MIH. However, it is presently unknown if the reduction in resting SBP following daily exposure, is coupled with reduced SBP responses during and after acute exposure to MIH. Methods: Participants with obstructive sleep apnea (OSA) and hypertension (n = 10) were exposed to twelve 2-minute bouts of MIH/day for 15 days. A control group (n = 6) was exposed to a sham protocol during which compressed air (i.e., FIO2 = 0.21) was inspired in place of MIH. Results: The hypoxic ventilatory response (HVR) and hypoxic systolic blood pressure response (HSBP) increased from the first to the last hypoxic episode on the initial (HVR: 0.08 ± 0.02 vs. 0.13 ± 0.02, P = 0.03; HSBP: 0.13 ± 0.04 vs. 0.37 ± 0.06, P < 0.001) and final (HVR: 0.10 ± 0.01 vs. 0.15 ± 0.03, P = 0.03; HSBP: 0.16 ± 0.03 vs. 0.41 ± 0.34, P < 0.001) day. The magnitude of the increase was not different between days (P ≥ 0.83). Following exposure to MIH, minute ventilation and SBP was elevated compared to baseline on the initial (MV: 16.70 ± 1.10 vs. 14.20 ± 0.28, P = 0.01; SBP: 167.26 ± 4.43 vs. 151.13 ± 4.56, P < 0.001) and final (MV: 17.90 ± 1.25 vs. 15.40 ± 0.77, P = 0.01; SBP: 156.24 ± 3.42 vs. 137.18 ± 4.17, P < 0.001) day. The magnitude of the increases was similar on both days (P ≥ 0.414). Despite these similarities, blood pressure at baseline and at other time points during the MIH protocol was reduced on the final compared to the initial day (P ≤ 0.005). Conclusion: The ventilatory and blood pressure responses during and following acute MIH were similar on the initial and final day of exposure. Alternatively, blood pressure was down regulated, while ventilation was similar at all time points (i.e., baseline, during and following MIH) after daily exposure to MIH.